The Sun, The Moon, and The Earth: A Screenplay Focusing on the Depth of Mid-Life Crisis in the Eye of an Indonesian Housewife - Christine Viena Karsono; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2024)
This creative work focuses on empowering Indonesian housewives, particularly those navigating transformative life challenges in their middle years. It champions complete autonomy in life decisions, ambitions, and goals, countering societal and familial expectations. The work also aims to highlight the vibrancy and aspirations of middle-aged women, combating societal invisibility and fostering a broader understanding of their diverse experiences. This work also seeks to present perspectives from marginalized groups, emphasizing middle-aged women often overlooked by society, through Indonesian cinema. The creative thesis aspires to inspire gender equality by amplifying women's experiences and advocating for their rights while challenging and reshaping traditional gender norms. Ultimately, this screenplay aims to influence perceptions both within the film industry and broader society, fostering an inclusive environment that values and encourages aspirations regardless of age or gender.